2016
DOI: 10.1186/s12886-016-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of selective laser trabeculoplasty for open-angle glaucoma

Abstract: BackgroundTo analyze the results of repeat selective laser trabeculoplasty (SLT).MethodsInclusion criteria: participants with primary or secondary open-angle glaucoma (excluding uveitic) who had undergone SLT 360° (SLT 1) with diminution of response over time followed by repeat SLT 360° (SLT 2). Six months of follow-up were required and at least 6 months in between SLT 1 and 2. The main outcome measures were IOP reduction at 6 and 12 months and a comparison of the response between SLT 1 and 2.ResultsOne hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 27 publications
3
44
0
2
Order By: Relevance
“…Several studies have already suggested that SLT is repeatable (Lai et al 2004;Hong et al 2009;Ayala et al 2011;Bovell et al 2011). Intraocular pressure (IOP) lowering effect after repeat SLT has been shown to be similar to that of the initial SLT (Francis et al 2016;Phillis & Bourke 2016;Polat et al 2016). In our study, 10 eyes (6.9%) needed a retreatment after a mean of 13.7 months.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have already suggested that SLT is repeatable (Lai et al 2004;Hong et al 2009;Ayala et al 2011;Bovell et al 2011). Intraocular pressure (IOP) lowering effect after repeat SLT has been shown to be similar to that of the initial SLT (Francis et al 2016;Phillis & Bourke 2016;Polat et al 2016). In our study, 10 eyes (6.9%) needed a retreatment after a mean of 13.7 months.…”
Section: Discussionmentioning
confidence: 98%
“…Repeatability of SLT has been studied and considered feasible in suitable patients requiring further IOP reduction. [7][8][9][10][11][12][13][14] However, many of these studies are retrospective and limited by small sample sizes and lack predefined retreatment criteria. In addition, in all but 1 of these studies, 13 SLT was used as an adjunctive treatment in patients already receiving topical IOP-lowering treatment.…”
mentioning
confidence: 99%
“…Third, the authors did not mention the time interval between the primary SLT and the repeat SLT/ALT. Francis et al 4 found that a shorter time period between the initial and repeat SLT resulted in statistically significant higher success rates. Therefore, we feel that the authors should have mentioned the time interval between the primary SLT and repeat SLT/ALT while assessing the effectiveness of repeat trabeculoplasty.…”
Section: To the Editormentioning
confidence: 99%